Study of the Distribution of Photoassimilates in Tomato (Lycopersicon esculentum Mill) - Grimaldi, María Cecilia (2003)
With the aim of evaluating the distribution of assimilates in tomato (Lycopersicon esculentum Mill), a trial under greenhouse was carried out with plants in hydroponic solution. The treatments were: H1; H2 and H3: Controls with the first, second and third leaf (among the first and the second truss) supplied with glucose [ C 14 (U) ] respectively H4: Pruning of the third leaf between trusses and the second leaf supplied. The pruning was done 25 days after the anthesis of the first cluster, the leaves were supplied in all treatments. 24 hours later, the plants were fractionated in root, shoot, basal leaves, expanded leaves, non expanded leaves, 1st , 2nd and 3rd trusses and apex. The plant material remained in stove up to constant weight. The samples were digested with OHNa 9N, homogenized, and scintillating solution Bray + cab-o-sil at 5% was added. The activity of the samples were measured in a Beckman LS 100 C liquid scintillation counter. The pruning of the third leaf modified the pattern distribution of assimilates in the plant. The group of clusters were the most important sinks in all treatments, reaching the highest value in H4 (70%). The stem was an important sink in all treatments. The highest contribution to it (30%) was done by the second leaf (H2). The removal of the third leaf increased the amount of assimilates entering the fruits and decreased the amount of glucose entering the stem.